Lie in wait : a novel - Rickstad, Eric (Witness, an imprint of HarperCollins Publishers, 2015)
Even in a quiet Vermont town, unspeakable acts of the past can destroy the peace of the present. In the remote pastoral hamlet of Canaan, Vermont, a high-profile legal case shatters the town's sense of peace and community. Anger simmers. Fear and prejudice awaken. Old friends turn on each other. Violence threatens. So when a young teenage girl is savagely murdered while babysitting at the house of the lead attorney in the case, Detective Sonja Test believes the girl's murder and the divisive case must be linked. However, as the young detective digs deeper into her first murder case, she discovers sordid acts hidden for decades, and learns that behind the town's idyllic façade of pristine snow lurks a capacity in some for great darkness and the betrayal of innocents. And Sonja Test, a mother of two, will do anything to protect the innocent.